Climatic stresses and adaptation options for South Asian wheat: A systematic literature review - Chakrabarti, Bidisha; Bhatia, A.; Deo, Aniket; Maitreya,; Jain, N.; Kumari, Venugopalan Visha; Chitiprolu, Anantha Rama Rao; Aggarwal, P. K. (Frontiers in Agronomy, 2025)
IntroductionWheat in South Asia faces multiple climatic stresses. This study systematically reviews the effects of these hazards on wheat and identifies adaptation options to reduce their impact on productivity.MethodsLiterature searches were conducted using academic databases such as Scopus and Web of Science, along with South Asian sources. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement was followed for quantitative synthesis of the literature.Results and discussionBibliometric analysis of the studies revealed that, heat stress and water stress are major climatic hazard affecting wheat crop of this region. The terminal heat stress was also highlighted in recent publications. Meta-analysis of the extracted data (401 data points) from selected publications (57 papers) provided new evidence on the suitability of different adaptation options under heat and water stress condition in different agroecological regions of South Asia. It was observed that under heat stress condition, adoption of heat tolerant varieties, early sowing and conservation agriculture (CA) practices increased the yield by 13.2%, 16.3% and 8.6%, respectively. Under water stress, yield improvement was 24.7% with growing drought tolerant varieties, 37.8% with CA practices and 13.7% with application of additional irrigation. The overall effectiveness of growing heat and drought tolerant varieties across agroecological zones followed the order CWZ > NEPZ > PZ > NWPZ. The CWZ and NEPZ exhibited the greatest yield gains, driven by the strong positive response to heat-tolerant varieties. In case of early sowing by 7-10 days, the effectiveness will follow the order NEPZ > NWPZ > CWZ. Overall, these findings highlight the importance of considering regional climatic conditions when designing adaptation strategies to enhance wheat productivity under rising temperatures.